2008
DOI: 10.1515/jbcpp.2008.19.1.1
|View full text |Cite
|
Sign up to set email alerts
|

The effects of compound 45/80, morphine, and mast cell depletion on electroshock seizure in mice

Abstract: We concluded that compound 48/80 (1) penetrates into the central nervous system to produce a central effect; (2) acts as pro-convulsive, and (3) paradoxically augments the anticonvulsive action of morphine, likely caused by the ability of the compound to increase the permeability of blood-brain barrier for morphine or by the release of histamine from mast cells in the brain, acting as anticonvulsant through the stimulation of H1 receptors or both. The precise mechanism of the increased death rate by C48/80 or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Because of their location at the host environment interface of the brain, as well as their ability to communicate via lymphatics, it seems reasonable to speculate that mast cells serve a unique duty of long-distance delivery of small quantities of mediators that they sense in the blood and the CSF. Mast cells are also known for their ability to recruit other immune cells to sites of action, and have been proposed as major immune regulators in multiple sclerosis, seizure induction, and CNS infection (Sayed et al, 2010; Skaper et al, 2013; Yillar and Kucukhuseyin, 2008). …”
Section: Introductionmentioning
confidence: 99%
“…Because of their location at the host environment interface of the brain, as well as their ability to communicate via lymphatics, it seems reasonable to speculate that mast cells serve a unique duty of long-distance delivery of small quantities of mediators that they sense in the blood and the CSF. Mast cells are also known for their ability to recruit other immune cells to sites of action, and have been proposed as major immune regulators in multiple sclerosis, seizure induction, and CNS infection (Sayed et al, 2010; Skaper et al, 2013; Yillar and Kucukhuseyin, 2008). …”
Section: Introductionmentioning
confidence: 99%
“…More importantly, mast cells have been implicated in the pathogenesis of seizures. One study using a mouse model showed that the non-allergic mast cell trigger compound 48/80 significantly increased the rate of seizures in mice induced by electric shock, and this effect was eliminated in mast cell-depleted mice [30]. Moreover, the mast cell trigger neurotensin (NT) [31] can facilitate N -Methyl-D-aspartate (NMDA)-induced excitation of cortical neurons [32] and seizure activity in rodents [33].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, another study showed that both acute and subchronic administration of sodium cromoglycate during the post‐status epilepticus period reduced neuronal damage and numbers of spontaneous generalized seizures in a lithium‐pilocarpine model of status epilepticus in rats (Valle‐Dorado et al., 2018). However, compound 48/80 has also been reported to exhibit pro‐convulsive effect by increasing seizure rates in an electroshock seizure model in mice (Yillar & Küçükhüseyin, 2008). By contrast, in the same study, compound 48/80 also enhanced the anti‐convulsive effect of morphine and increased the survival of mice with seizures (Yillar & Küçükhüseyin, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…However, compound 48/80 has also been reported to exhibit pro‐convulsive effect by increasing seizure rates in an electroshock seizure model in mice (Yillar & Küçükhüseyin, 2008). By contrast, in the same study, compound 48/80 also enhanced the anti‐convulsive effect of morphine and increased the survival of mice with seizures (Yillar & Küçükhüseyin, 2008). Our results are in contrast to those previous studies, except for part of Yillar and Kücük Hüseyin's study.…”
Section: Discussionmentioning
confidence: 99%